Cell cycle phase distribution analysis in chronic lymphocytic leukaemia: a significant number of cells reside in early G1-phase. Issue 7 (1st September 2006) - Obermann, Ellen C; Went, Philip; Tzankov, Alexandar; Pileri, Stefano A; Hofstaedter, Ferdinand; Marienhagen, Joerg; Stoehr, Robert; Dirnhofer, Stephan
Abstract : Background and Aims: Chronic lymphocytic leukaemia (CLL) is a frequent non-Hodgkin lymphoma characterised by a heterogeneous clinical course. Assessment of cell cycle phase kinetics might be important for prediction of clinical behaviour and prognosis. Methods: Distribution of neoplastic cells in CLL within the cell cycle was evaluated by determining the labelling indices (LI, i.e. percentage of positive cells) of markers specific for late G1-phase (cyclin E), S-phase (cyclin A), and G2/M-phase (cyclin B1), and Mcm2, a novel marker of proliferative potential, in a large cohort of patients (n = 79) using tissue microarray (TMA) technology. Utilising a combination of these markers, an algorithm was developed—subtracting the combined LIs of cyclin E, cyclin A and cyclin B1 from the LI of Mcm2—to determine the percentage of tumour cells residing in early G1-phase, which is probably a critical state for the malignant potential of CLL. Results: 27.11% of cells had acquired proliferative potential as indicated by expression of Mcm2. Only a small number of cells were found to be in late G1-phase (7.16%), S-phase (3.31%) or G2/M-phase (0.98%), while 15.66% of cells were considered to be in early G1-phase. Conclusion: Cell cycle phase distribution can easily be assessed by immunohistochemistry in routinely processed paraffin-embedded specimens. A large number of neoplastic cells in CLL have proliferative potential, with a significant sub-population residing in early G1-phase. Estimates of these cells may identify cases likely to exhibit a more aggressive biological behaviour and adverse clinical course.